Analisis Komparasi Biaya Dan Pendapatan Usahatani Padi Organik dan Anorganik Di Desa Karang Sari Belitang III OKU Timur - Mahidin Fahmie; Aisah; Iswan (Jurnal Bakti Agribisnis, 2023)
Indonesia has a wealth of tropical biological resources, an abundance of sunlight, water and soil, as well as a culture of people who respect nature. This is what makes Indonesia has great potential for organic farming. The demand for organic rice in Indonesia continues to increase every year. In 2001 organic rice production was 1,180 tons, while in 2004 organic rice production increased to 11,000 tons. In 2005 Indonesia's organic rice market reached 28 billion rupiah with a growth of around 22 percent per year. Organic farming systems are increasingly popular lately due to the failure of inorganic farming systems in maintaining land and environmental sustainability in the long term. This is because in its application, the agricultural system is very dependent on the use of chemical substances such as urea, TSP, ZA, pesticides and so on so that in the long run it will have an impact on damage to agricultural land which will ultimately reduce productivity. Karang Sari Village, one of the villages in Belitang III District, OKU Timur Regency, where the majority of the population has a livelihood as lowland rice farmers, seeks organic rice cultivation without using chemical fertilizers or pesticides, but most farmers still grow rice conventionally (inorganic).